Academic detailing interventions for opioid-related outcomes: a scoping review - Victoria Kulbokas; Kent A Hanson; Mary H Smart; Monika Rao Mandava; Todd A Lee; A Simon Pickard (BioExcel Publishing Ltd, 2021)
Background: Academic detailing (AD) is a tailored, interactive educational outreach intervention that may improve patient outcomes. Insight into the design of AD interventions and the extent to which they are effective can help inform future AD-based programmes. The objective of this scoping review was to characterize opioid-focused AD interventions and describe their findings. Methods: A scoping review focused on AD interventions for opioids was conducted in PubMed, EMBASE and CINAHL databases through July 1, 2021. Studies were eligible for inclusion if written in English, included interactive opioid-focused educational interventions, and were conducted either in person, virtually or via telephone. Four independent reviewers reviewed titles and abstracts. Data extraction from full-text publications was completed using a standardized form. Results: Of 6086 articles initially identified, 22 articles met the inclusion criteria and 20 unique interventions were identified. The AD intervention was either delivered one-on-one (n=16) or in a small, interactive group setting (n=4). AD interventions varied in design. Effectiveness was evaluated in terms of opioid and naloxone prescribing rates, provider knowledge gaps, provider adherence to guidelines, and intervention feasibility. Sixteen (80%) interventions resulted in statistically significant improvement in one or more outcomes. Conclusion: Generally, opioid-related AD was effective and programmes were primarily conducted one-on-one between pharmacists and primary care providers for 16-30 minutes. A variety of metrics and outcomes were used to assess the success/effectiveness of AD interventions, which is an important consideration in future studies as no single metric captures the effectiveness of an educational outreach-based intervention for pain management.